Covid 19 Vaccine - boon or a bane? - Kasturi Ravinder Reddy1 , Samkisha Earna2 (Perspectives In Medical Research, 2020)
The global struggle against corona virus disease 2019(COVID19) is now in its 8th month since the pandemic virus SARS –COV2 has first emerged.The severe economic,personal and psychological adverse effects of shutdowns and social distancing make these effective preventive measures challenging to sustain long term.Safe and effective COVID-19 vaccine could lead to a level of global immunity that stops the pandemic.This is the anti COVID-19 intervention most public health leaders and many people long for the most